Nutritional education in the primary prevention of osteoporosis in perimenopausal and postmenopausal women - Woźniak-Holecka, Joanna; Sobczyk, Karolina (Menopause Review/Przegląd Menopauzalny, 2014)
Osteoporosis affects millions of people in the whole world and brings about far-reaching physical and psycho-social consequences for patients and financial ones for the health care system, and therefore it is classified as one of public health problems and treated as a social disease. Women belong to the increased osteoporosis illness risk group due to lower top bone mass reached earlier in life as compared to men and due to hormonal changes occurring in the menopausal period, which affect loss of the bone mineral density (BMD). Limitation of the osteoporosis-related financial and social costs increase requires efficient preventive actions on the level of early, primary, secondary or tertiary prevention. At all the four osteoporosis prevention phases, the crucial role is played by health education and nutrition education, the latter being the key element of the former one. The nutritional education purpose is to acquaint patients with nutrition recommendations that are the basic element of the osteoporosis prevention and to make them change their nutrition habits, which will improve their osseous metabolism. The education should be based on results of the latest scientific researches and focus on recommendations relating to proper supplementing of calcium and vitamin D, simultaneously including all the other nutrition components, necessary to decrease the osteoporosis risk. The primary prevention oriented to a specific group at risk for osteoporosis, including peri- or postmenopausal women, should be provided in cooperation with the different levels’ medical professionals and it should focus on causing positive changes in patients both as regards nutrition habits and physical activities.